2015
DOI: 10.1248/cpb.c15-00088
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Phase Separation in Mixed Preparations of Moisturizing Cream and Steroid Ointment after Centrifugation

Abstract: A mixed preparation consisting of a water-in-oil emulsion-type moisturizing cream and a steroid ointment is frequently prescribed for the treatment of atopic dermatitis. We have investigated the compatibility of moisturizing creams and ointments because there are concerns regarding the physical stability of these mixed preparations. The key technology used in this study was magnetic resonance imaging (MRI). A commercial moisturizing cream and white petrolatum or clobetasone butyrate (CLB) ointment samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…We previ- ously investigated the physical stability of a mixed preparation consisting of a moisturizing cream and a steroid ointment for use in the treatment of atopic dermatitis. 16) In the course of the previous study, we applied this technique and successfully visualized the heterogeneous distributions of water and oil in the phase-separated samples. Based on that study, we tried to visualize the distribution of specific compounds in the sample using the CSS image.…”
Section: Resultsmentioning
confidence: 99%
“…We previ- ously investigated the physical stability of a mixed preparation consisting of a moisturizing cream and a steroid ointment for use in the treatment of atopic dermatitis. 16) In the course of the previous study, we applied this technique and successfully visualized the heterogeneous distributions of water and oil in the phase-separated samples. Based on that study, we tried to visualize the distribution of specific compounds in the sample using the CSS image.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] MRI is a popular molecular imaging method using the principle of NMR. 14) As well as nondestructive monitoring of a sample, it enables visualization of the molecular mobility of a sample using magnetic resonance (MR) parameters.…”
Section: )mentioning
confidence: 99%
“…From our previous studies, it has been confirmed that T 2 maps are a powerful tool to detect phase separation in pharmaceutical emulsions. 10,11,15) As far as oil-in-water (o/w)-type emulsion is concerned, the state of water is substantially changed depending on its surroundings.…”
Section: Effects Of Surfactants On the Emulsion Stability Of The Creammentioning
confidence: 99%
“…10) These observations suggest that the stability of a preparation is diminished by mixing creams and ointments. It is therefore necessary to determine objectively and scientifically the types of blending variations that are induced by mixing different * To whom correspondence should be addressed.…”
mentioning
confidence: 99%